Analysis of the RBA implementation and the preparation of an audit program at the Ministry of Villages, Development of Disadvantaged Regions and Transmigration - Nugraheni, Nur Meilani Tri; Pamungkas, Bambang (Badan Pemeriksa Keuangan Republik Indonesia, 2021)
Risk-Based Audit (RBA) is an audit method that applies a risk approach in its implementation. By applying the RBA method, it is expected that an audit can be performed effectively and efficiently, thus producing maximum audit results. This study aims to analyze the implementation of RBA upon audits conducted by The Audit Board of Indonesia (BPK). Furthermore, this study analyzes the preparation of an Audit Program in line with the previously determined RBA. The research framework uses Agency Theory which emphasizes the relationship between management and principal. To ensure that management does not perform any manipulation, an independent third party must conduct the audit. This study applied a qualitative research methodology with a case study approach at BPK. The author expects to dig deeper into the application and implementation of RBA within BPK by using the case study approach support by audit documents and interviews with BPK Audit Team. The results showed that the implementation, performance, and monitoring of RBA by the BPK Audit Team were in line with the instructions and guidelines set by BPK.